SOSIALISASI PEMBERIAN BOLU KUKUS DAUN KATUK UNTUK MENINGKATKAN PRODUKSI ASI PADA IBU MENYUSUI DI PUSKESMAS PANTAI CERMIN KABUPATEN SERDANG BEDAGAI - Raini Panjaitan; Reno Irwanto; Nadia Husna; Wira Maria Ginting; Desri Meriahta Girsang; Andreais Boffil Cholilullah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
Abstrak Pemberian air susu ibu secara eksklusif merupakan pilihan terbaik untuk bayi yang baru lahir hingga usia 2 tahun. Masalah yang timbul pada ibu menyusui adalah produksi jumlah ASI yang tidak maksimal. Salah satu penyebab masalah tersebut adalah asupan gizi yang rendah sehingga banyak bayi yang kebutuhan gizinya kurang terpenuhi. Pelaksanaan sosialisasi pengabdian masyarakat ini telah dilakukan selama empat hari di Puskesmas Pantai Cermin. Tujuan kegiatan ini adalah untuk meningkatkan produksi ASI ibu menyusui melalui pemberian bolu kukus daun katuk. Ibu menyusui diberikan 1 porsi bolu kukus daun katuk yang terdiri dari 3 potong yang masing-masing beratnya 15 gram selama empat hari. Pada hari pertama tim pelaksana melakukan edukasi tentang ASI melalui ceramah dan diskusi serta memperkenalkan produk bolu kukus daun katuk dilanjutkan dengan demonstrasi pembuatan bolu kukus daun katuk dan pemberian bolu kukus daun katuk kepada peserta. Pemberian bolu kukus daun katuk dilanjutkan hingga hari ke empat dan lembar observasi tentang frekuensi menyusui dibagikan setiap hari. Berdasarkan sosialisasi ini didapatkan hasil bahwa ibu menyusui mengalami peningkatan frekuensi menyusui dalam 24 jam. Disimpulkan bahwa produk bolu kukus daun katuk efektif meningkatkan produksi ASI. Abstract Exclusive breastfeeding was the best choice for newborns up to 2 years of age. The problem that arises in breastfeeding mothers was the production of the amount of milk that was not optimal. One of the causes of this problem was low nutritional intake so that many babies had less nutritional needs. This community service outreach has been carried out for four days at the Pantai Cermin Health Center. The purpose of this activity was to increase breastfeeding production of breastfeeding mothers through the provision of katuk leaf steamed sponge. Breastfeeding mothers are given 1 serving of katuk leaf steamed sponge, which consists of 3 pieces, each pieces was 15 grams for four days. On the first day, the implementation team conducted education about breast milk through lectures and discussions and introduced the katuk leaf steamed sponge product, followed by a demonstration of making katuk leaf steamed sponge and giving katuk leaf steamed sponge to the participants. The distribution of katuk leaf steamed sponge was continued until the fourth day and the observation sheet on the frequency of breastfeeding was distributed every day. Based on this socialization, it was found that breastfeeding mothers had an increasing of the frequency of breastfeeding within 24 hours. It was concluded that the katuk leaf steamed sponge product was effective in increasing breast milk production. Abstract Exclusive breastfeeding was the best choice for newborns up to 2 years of age. The problem that arises in breastfeeding mothers was the production of the amount of milk that was not optimal. One of the causes of this problem was low nutritional intake so that many babies had less nutritional needs. This community service outreach has been carried out for four days at the Pantai Cermin Health Center. The purpose of this activity was to increase breastfeeding production of breastfeeding mothers through the provision of katuk leaf steamed sponge. Breastfeeding mothers are given 1 serving of katuk leaf steamed sponge, which consists of 3 pieces, each pieces was 15 grams for four days. On the first day, the implementation team conducted education about breast milk through lectures and discussions and introduced the katuk leaf steamed sponge product, followed by a demonstration of making katuk leaf steamed sponge and giving katuk leaf steamed sponge to the participants. The distribution of katuk leaf steamed sponge was continued until the fourth day and the observation sheet on the frequency of breastfeeding was distributed every day. Based on this socialization, it was found that breastfeeding mothers had an increasing of the frequency of breastfeeding within 24 hours. It was concluded that the katuk leaf steamed sponge product was effective in increasing breast milk production.